PENGARUH LKS TERINTEGRASI MATERI GEMPA BUMI PADA KONSEP USAHA, ENERGI, MOMENTUM, DAN IMPULS TERHADAP KOMPETENSI FISIKA KELAS XI SMAN 4 PADANG DALAM MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE (SSCS) PROBLEM SOLVING - Nurul Ilmarsah Rustam; Ahmad Fauzi; Syafriani Syafriani (Universitas Negeri Padang, 2016)
The nature of Physics is a science that studies contextual and authentic natural phenomena. However, the fact shows the ability of students in to critically, the motivation, and the problem-solving ability are still in low category. These problems can be solved by many ways, one of them integrating earthquake material into Physics material and also by applying SSCS Problem Solving in learning process. All of these are provided interestingly as a teaching material in a form of LKS (Student Worksheet). The integration of earthquake material is intended to form a character of disaster preparedness to students. The purposes of this research are: 1) To investigate the influence of LKS that integrates earthquake material, 2) To investigate the contribution of LKS that integrates earthquake material, 3) To investigate the influence of SSCS Problem Solving model toward Physics competencies in Class XI of SMAN 4 Padang. It is a Quasy-Experiment research with Randomized Subjects Post Test Only Control Group Design. The population of the research is all of Class XI MIA registered at 2015/2016 year of study. The technique of sampling is done by using Purposive Sampling in which Class XI MIA 1 as the experimental class and X1MIA 2 as the control class. The data analysis in this research used test of normality; homogeneity; the similarity of two average in real stage 0,05; linear regression test; and the results of these research are 1) There’s an increase on student’s competence as the result of integrating earthquake into Physic’s leraning material; 2) The contribution of LKS that integrated earthquake material to influence the student’s competency affective 63.62%, 81.02% to knowledge, and skill 42.33% ; 3) There are influence of SSCS Problem Solving model toward Physics competencies of Class IX of SMAN 4